Meningkatkan Minat dan Hasil Belajar KD Mengkonsumsi Makanan dan Minuman yang Halal dan Menjauhi yang Haram dengan Metode Gallery Walk pada Siswa Kelas VIIIA Semester 2 SMP Negeri 4 Purworejo - Siti Saudah (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
This research is based on the importance of increasing KD interest and learning outcomes in consuming halal food and drinks and avoiding haram ones using the Walk Gallery method in Class VIIIA Semester 2 of SMP Negeri 4 Purworejo. The aim of this research is to increase PAIBP's interest and learning outcomes in the material Consuming Halal Food and Drinks and Avoiding Haram for class VIIIA Semester 2 students at SMP Negeri 4 Purworejo. The method used in this Classroom Action Research is the Walk Gallery learning method. The subject of this Class Action Research is class VIIIA of SMP Negeri 4 Purworejo for the 2019/2020 academic year. The number of students is 32 consisting of 12 boys and 20 girls, namely from January to March 2020 in the even semester. Each cycle consists of planning, implementation, observation and reflection. The research procedure consists of pre-research, cycle one planning, implementation of cycle one actions, observation cycle one, reflection cycle one. This research produces the following conclusions. (1) The Gallery Walk method can increase interest in learning, namely activating all students in the learning process by visiting observers to other galleries and representatives of gallery attendants to exchange information on the material being discussed. This can be seen from the increase in interest in listening to explanations in cycle I from 84%, cycle II to 100%, interest in doing assignments from 78% to 93%, interest in seeking information from 68% to 78%, and interest in participating in groups from 81% to 93%. (2) Using the Gallery Walk method can improve student learning outcomes. Students' learning completeness and absorption of subject matter always increases, starting in cycle I, 75% of students have completed learning with an absorption capacity of 79.22%, then in cycle II there has been an increase, namely 100% of students have completed learning with an absorption capacity of 87%. .03%.